CONSUMPTION COMPARISON IN ISLAMIC AND CONVENTIONAL PERSPECTIVES (International Conference on Social and Islamic Studies, 2022)
Today's human nature is strongly influenced by the progress of civilization, especially the influence of the digitalization era which directly affects human behavior, especially in consuming products. The consumptive nature seems to be a culture of urban society which tends to exhibit the israf . The ability to sort out needs and desires is certainly a solution that can solve this israf problem. Islamic studies on consumption are very important, so that someone is careful in using wealth or spending wealth. So the most important thing in this case is the method of use which should lead to options (preferences) that contain benefits and maslahah (good and useful), so that the wealth is utilized in a way that is ma'ruf for the prosperity and benefit of individuals, society and the people as a whole. thorough. The method used in this study is a qualitative method, namely by comprehensively examining phenomena originating from literature, journals and other valid sources. The purpose of this study, apart from increasing knowledge in Islamic economics, is also to find out and clarify the comparative theory of consumption in Islamic economics and conventional economics, as well as to study the problems of both. The value obtained in Islamic consumption, Muslims will get more satisfaction when consuming halal goods compared to unlawful goods. In contrast to conventional consumption theory which does not regulate the law of halal-haram goods or services. In Islamic consumption theory, a Muslim does not only manage worldly needs but also aims to achieve falah (glory and victory in life). Individuals should be wise in consuming all needs by paying attention to priorities, setting aside infaq, sadaqah and consuming halal goods to achieve the pleasure of Allah SWT.